'Time to move on' or 'taking more time'? How disregarding multiple perspectives on time can increase policy-making conflict. (March 2018) - Wolf, EEA; Van Dooren, Wouter
This article argues that when different perspectives on time remain disregarded in a public policy debate, policy-making conflict can increase. We present an in-depth qualitative analysis of media articles from 2005, 2009, and 2014 in the debate surrounding the contested 'Oosterweel connection, ' a multibillion-euro infrastructure project in Antwerp (Belgium). Although concerns of time management motivated arguments to speed up the policy-process, the insensitivity of policy-makers to multiple perspectives on time increased conflict. Firstly, while administrative actors reasoned mainly from a procedural time perspective and saw time as scarce, citizens reasoned mostly from an impact-based time perspective and saw time as abundant. A binary debate on policy-making tempo (high versus low) ensued. Secondly, political actors often reasoned from political perspectives on time. Their actions, which were intended to appease, did not end the binary debate and sometimes reinforced it. As the debate on the Oosterweel connection persisted, parties increasingly believed that not only were their infrastructure goals incompatible, but so too were their goals for time management. This increased conflict.